Harmonizing sustainability assessment in seaports: A common framework for reporting environmental performance indicators. (1st March 2021) - Rodrigues, V.; Russo, M.; Sorte, S.; Reis, J.; Oliveira, K.; Dionísio, A.L.; Monteiro, A.; Lopes, M.
Abstract: The continuous world population growth, followed by current globalization levels, raises concerns towards sustainable development, including the sustainability of organizations. In recent decades, organizations have been increasing their commitment to sustainability. In particular, port organizations are aware of their most critical economic, environmental and social impacts, due to the continuous growth of the sector. Performance indicators are an important tool to assess the environmental performance of a port. In this paper, we aim to recognize the role of these indicators on the sustainability assessment of port organizations. For that purpose, we apply the benchmarking technique to compare the performance of distinct European seaports using environmental performance indicators from the Global Reporting Initiative consolidated guidelines. The indicators most representative of port activities are established and quantified considering the available data for the period between 2008 and 2017. The difficulties associated with the application of the benchmarking technique paves the way for guidelines towards the establishment of a common framework for reporting environmental indicators for the specific case of port organizations. Based on the benchmarking outcomes, we apply the environmental performance indicators to the Port of Aveiro to assess their effectiveness while suggesting adjustments to the existing indicators which are better suited for port activities. The outcomes of this study will provide port organizations with a common framework to report environmental sustainability, thus allowing for a better comparison of their environmental performance. Graphical abstract: Highlights: EPI provide a method to assess the environmental performance of seaports. GRI guidelines may be upgraded including new sectoral indicators for seaports. Comparison of distinct seaports' point out the need to report indicators using a common framework. Quantification of indicators may contribute to effectively improve the performance of seaports.